Comparative efficacy of six programmed cell death Protein-1 inhibitors as first-line treatment for advanced non-small cell lung cancer: a multicenter retrospective cohort study - Chen, Siyuan; Li, Tao; Yang, Wenyu; Wang, Ting; Qin, Yuhui; Du, Zhijuan; Li, Yanan; Cui, Pengfei; Hu, Yi; Liu, Zhefeng (Frontiers in Pharmacology, 2024)
The purpose of this study was to assess the comparative efficacy of six programmed cell death-1 inhibitors (nivolumab, pembrolizumab, sintilimab, tislelizumab, toripalimab, and camrelizumab) that have been used as first-line therapy for Chinese patients with advanced non-small cell lung cancer (NSCLC), which remains unclear. We determined the differences in efficacy by observing patient survival data, with the goal of informing future treatment options. Retrospective data analysis from June 2015 to April 2023 included 913 patients across six groups: nivolumab (123, 13.5%), pembrolizumab (421, 46.1%), sintilimab (239, 26.1%), tislelizumab (64, 7.0%), toripalimab (39, 4.3%), and camrelizumab (27, 3.0%). The median progression-free survival (PFS) for each group was 16.0, 16.1, 18.4, 16.9, 23.7, and 12.8 months, and the median overall survival (OS) was 33.7, 36.1, 32.5, not reached, 30.9, and 46.0 months for the nivolumab, sintilimab, pembrolizumab, tislelizumab, toripalimab, and camrelizumab groups, respectively. While differences existed in the objective response rates among groups (P<0.05), there were no significant differences (all P>0.05) in PFS or OS. The findings suggest comparable efficacy among these PD-1 inhibitors for NSCLC treatment, underscoring their collective suitability and aiding treatment decisions.